Studují spolu Vzájemné učení mezi vysokoškolskými studenty kombinovaných studií a možnosti jeho podpory - Brücknerová, Karla (Masaryk University Press, 2021)
Title in English: Studying together: Peer learning among part-time students in higher education, and support possibilities. The book presents peer learning among part-time students as an essential part of their higher education experience. It summarizes the research that indicates that students' achievement, well-being, and study engagement are related to peer learning. Possibilities for supporting peer learning are discussed. Qualitative research of peer learning among part-time students studying for educational degrees offers descriptions of contextual influences and peer learning situations. Based on patterns of occurrence of peer learning situations, three types of peer learning among part-time students are defined: studying beside peers, studying together with peers, and studying due to peers. Each type brings specific benefits and requires distinct support.